Ask Question
14 April, 04:03

If you were to move use the substitution method to solve the following system choose the new equation after the expression equivalent to ask from the second equation is subject to dig into the first equation.

2x-3y=-29

x+4y=13

A) 2 (4y+13) - 3y=-29

B) 2 (-4y+13) - 3y=-29

C) 2x-3 (4y+13) = -29

D) 2x-3 (-4y+13) = -29

+1
Answers (1)
  1. 14 April, 05:28
    0
    Solve x+4y = 13 for x by subtracting 4y from both sides.

    We end up with x = - 4y+13.

    Since x and - 4y+13 are the same, we can replace every x in the first equation with - 4y+13

    2x-3y = - 29

    2 (x) - 3y = - 29

    2 (-4y+13) - 3y = - 29 ... x is replaced with - 4y+13

    The answer is choice B
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “If you were to move use the substitution method to solve the following system choose the new equation after the expression equivalent to ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers